Employed Mothers: Job Satisfaction and Self-Esteem - Sinacore-Guinn, Ada L. (Canadian Journal of Counselling and Psychotherapy, 2007)
The goal of this research is to examine how certain demographic variables (e.g., occupation, age of children) affect job satisfaction and self-esteem in a sample of 138 employed mothers from a major city in the U.S. The results indicate that age, race, and employment status (parttime versus full-time) were significantly related to job satisfaction and self-esteem. At t he same time, education level, number and age of children, and marital status were not significantly related to job satisfaction and self-esteem. Mothers were not more satisfied with one occupation over another, but they did indicate discrepancies in their satisfaction with their pay and opportunities for promotion.. In summary, these women's occupational choice based on their motherhood status did not lead to higher levels of job satisfaction. Implications for counselling are discussed.